Impulsivity and alcohol expectancies: assessment of the acquired preparedness model for alcohol use in teenagers - Paternó Manavella, María Agustina (2019)
Introduction: Alcohol is the psychoactive substance with the highest levels of consumption among Argentinian teenagers. It is a concern, because 13% and 25% of teenagers show heavy episodic drinking ([HED]; i.e., 4/5 standard alcohol drinks in one drinking session for women and men, respectively). Two variables related to alcohol consumption are impulsivity (a multidimensional concept that includes several behaviors, such as being unable to inhibit a response, act without planning, difficulty on estimating consequences on a particular behavior, among others) and alcohol expectancies (beliefs about positive and negative effects of alcohol use on behavior, mood and emotions). The Acquired Preparedness Model (APM) integrates both variables by stating that people with higher levels of disinhibition are prone to learn the positive reinforcements of alcohol consumption, leading to higher levels of alcohol use. There are no studies that have examined the APM in Argentinian adolescents using a multidimensional model of impulsivity. Aim: To examine the mediational role of alcohol expectancies in the association between impulsivity (using a multidimensional model of impulsivity, the UPPS-P) and frequency of HED in teenagers from Buenos Aires (Argentina). Methodology: A sample of 427 high-school students (58% women, aged 13-18 years old [M=15.72+1.48]) from Buenos Aires (Argentina) took part of the study. Participants reported frequency of engaging in HED and measures to assess trait-like impulsivity (UPPSP) and alcohol expectancies. Results: HED is highly prevalent (i.e., close to half of teenagers) among this sample. Data showed adequate fit to the APM model (CFI = .980; p = .0318; RMSEA = .067 [IC 90 0.018, 0.121]). Specifically, results confirmed the mediational role of alcohol expectancies in the relationship between impulsivity and HED.